EVALUASI PROGRAM SKRINING STATUS TETANUS TOXOID WANITA USIA SUBUR DI JEMBER TAHUN 2010 - Abu Khoiri, Dewi Rokhmah, Ahmad Falih (Jurnal Kebijakan Kesehatan Indonesia, 2012)
Background: Cases and deaths due to Tetanus Neonatorum(TN) in Jember District within the period of 2005 to 2009 with aCase Fatality Rate (CFR) were greater than 50%. CFR with arate of more than or equal to 50% indicates a high share ofdeaths. Jember District Health Office implemented a screeningprogram for childbearing women’s TT status in early 2010.However, not until the end of 2010 there were already 6 casesand 3 deaths due to TN (CFR = 50%). This suggested that theimplementation of the screening program had already beenrunning but not optimal; thus, an evaluation for this programneeded conducting.Objective: To evaluate the screening program for childbearingwomen’s TT status by describing the capacity and motivationof personnel, implementation and results of the screeningprogram in Jember District in 2010.Method: This was a descriptive-evaluation study. It wasconducted in January-February 2011 in five health centers ofJember District. The population was midwives as persons incharge of implementing the screening program.Result: Most respondents (59%) had a moderate level ofcapacity. Most respondents had a high level of intrinsic andextrinsic motivation, namely 71% and 53%, respectively. Thescreening implementation for childbearing women’s TT statusby the respondents had not been in accordance with the twooperational procedures. The results of the screening programshowed that five health centers were still experiencing thesame problem, i.e., not identified TT status of all women andunmet target coverage of T5 childbearing women and T2 pluspregnant women.Conclusion: Technically, some obstacles in the implementationof the screening program are still present; therefore, there is aneed for conducting training procedures for the personnel ofthe screening program for childbearing women’s TT statusand conducting an evaluation for the program periodically andcontinuously.Keywords: evaluation, tetanus toxoid, childbearing women